RETHINKING TOURISM VILLAGES: HOW ECOLOGICAL JUSTICE SHAPES SUSTAINABLE DEVELOPMENT - Wibowo, Dwi Edi; Niami, Mutimatun (Faculty of Law, Universitas Pasundan, 2024)
Tourism village management plays a pivotal role in advancing sustainable development, particularly in rural areas endowed with rich biodiversity and natural resource potential. Ecological justice, which underscores equitable access to natural resources and shared responsibility in maintaining ecosystem balance, is a critical concept for ensuring sustainability in tourism village management. This study investigates the integration of ecological justice into tourism village management and examines the challenges and opportunities associated with its implementation. Utilizing a qualitative approach, the research explores strategies and policies that promote environmental sustainability while enhancing the welfare of local communities. The findings reveal that participatory approaches, environmental education, and policies rooted in local wisdom are essential for achieving ecological justice. The novelty of this study lies in its focus on ecological justice as a comprehensive framework that transcends economic considerations to incorporate ecological and social equilibrium. By proposing a model for sustainable tourism village management, this research contributes to the discourse on sustainable development, providing practical insights for policymakers and stakeholders in achieving long-term environmental and community welfare objectives.